Manifestation of multiphonon structure and orbitons in the tunnel spectra of manganites - Svistunov, V.M.; Leonova, V.N.; Belogolovskii, M.A.; Revenko, Yu.F. (Functional Materials, 2009)
The study results of the tunnel conductance of heterostructures formed by a silver tip and a doped Ag/La₀.₅₇Ca₀.₄₃MnO₃ manganite in the voltage region above manganite phonon and magnon frequencies are presented. Three maxima have been observed at energies corresponding to the peaks in the Raman spectra of LaMnO₃. It is supposed that the maxima are due to the interaction of tunneling electrons with excitations in the orbital subsystem of a degraded region nearby the metal-manganite interface. Представлено результати досліджень тунельної провідності гетероструктур, утворених срібним вістрям і легованим манганітом Ag/La₀.₅₇Ca₀.₄₃MnO₃, в області напруг вище фононних і магнонних частот манганітів. Знайдено три максимуми при енергіях, відповідmrх пікам у спектрах комбінаційного розсіяння LaMnO₃. Передбачається, що вказані максимуми обумовлені взаємодією тунелюючих електронів із збудженнями в орбітальній підсистемі деградованої області, що примикає до інтерфейсу метал манганіт. Представлены результаты исследований туннельной проводимости гетероструктур, образованных серебряным острием и легированным манганитом Ag/La₀.₅₇Ca₀.₄₃MnO₃, в области напряжений выше фононных и магнонных частот манганитов. Обнаружены три максимума при энергиях, соответствующих пикам в спектрах комбинационного рассеяния LaMnO₃. Предполагается, что указанные максимумы обусловлены взаимодействием туннелирующих электронов с возбуждениями в орбитальной подсистеме деградированной области, примыкающей к интерфейсу металл манганит.